Screening of some Sumatran medicinal plants and selected secondary metabolites for their cytotoxic potential against MCF-7 and HSC-3 cell lines - Husnunnisa, Husnunnisa; Ismed, Friardi; Bakhtiar, M. Taher; Ichwan, Solachuddin J. A.; Bakhtiar, Amri; Arbain, Dayar (Marmara University Press, 2019)
In continuation of our study of Sumatran plants and bioactivities of their constituents particularly their cytotoxic activities, we re-extracted lichen Stereocaulon graminosum Schaer (Stereocaulaceae), and isolated atranorin (1) and stictic acid (4).. These isolated compounds have been tested for their cytotoxic activities against human breast adenocarcinoma cancer cell (MCF-7) and human oral squamous carcinoma cancer cell (HSC-3) using MTT assay with a slight modification. Some methanolic extracts of the leaves of Elephantopus scaber, Piper betle, Andrographis paniculata, rhizomes of Boesenbergia pandurata, Alpinia galanga, Kaempferia galanga and isolated compounds; ethyl haematommate (2), olivatolic acid (3), deoxyelephantopin (5), andrographolide (6), hydroxychavicol (7), eugenol (8), curcumin (9), pinostrobin (10), pinocembrin (11), alpinetin (12), α-mangostin (13), angiopteroside (14), and stevioside (15) from Sumatran traditional medicinal plants have also been tested.